Proposal for the development of a Center for Aquaculture, Conservation and Export of Fan Shells 2012 – 2022 - Linares Vizcarra, Mitzi Lourdes Del Carmen (2021)
The present Feasibility proposal proposes, as an alternative to improve the development of aquaculture in the Tacna Region, the cultivation of the Concha de Abanico (Agropecten pupuratus), considering the commercial value and the international markets that present an unsatisfied demand.  The coastline of the Tacna Region presents physical-chemical and biological characteristics for the development of a cultivation program; Likewise, the coastal area offers a favorable bathymetry which is combined with the aforementioned, from which it follows that a period of 12 months will be obtaining the product in accordance with the requirements of international markets such as the case of France, USA and Japan.The project initially proposes 4 cultivation lines with 400 lanterns that after the unfolding processes will obtain about 1'104,000 units of fan shell, with sizes between 8 and 10 cm.The aquaculture project is extremely profitable since it is a development alternative for the Province of Ite, in the Tacna Region. Likewise, the export market for fan shells in Peru in terms of its consumption habit is extremely low, which is why the export of international markets is done.